1990s: Decade of Change - Caygill, David (Victoria University of Wellington Law Review, 2003)
As market principles took firmer hold in New Zealand public policy in the 1990s, ACC received close scrutiny and passed through three legislative revisions. The idea of opening ACC to competition from private insurance providers was moving up the policy agenda—and was briefly enacted in 1999, prior to a change in government. New management practices within ACC focused attention on cost containment, benefit levels, and experience-rated premiums for employers. This paper, by the current Chair of ACC, summarises the history of formal reviews, administrative changes, and legislative reforms across the decade, including the increasing emphasis on administrative efficiency.